Antibacterial Ingredients That Cause Diarrhea Can Be Made from Black, Green, and White Tea Extract (Camellia sinensis L.) - Akhmad Endang Zainal Hasan; Dimas Andrianto; Dadan Rohdiana; Heddy Julistiono; Muhamad Alvin Adriyan; Dadan Rohdiana (Universitas Djuanda, 2023)
One cause of diarrhea is a bacterial infection. Tea (Camellia sinensis) is a steeping drink that has the efficacy of treating diarrhea. This looks at goals to decide the effect of formulations of three tea extracts that act as antibacterial causes of diarrhea and decide the most appropriate maceration temperature. Extraction was carried out with water solvents at temperatures 70oC, 100oC, and 121oC. The disc method conducted an antibacterial test against E. coli and S. aureus. The most optimal temperature for producing the highest inhibitory zone is the temperature of 100oC. Tea extract temperatures of 100oC are used for antibacterial testing. BSLT test showed the LC50 value of 1800 µg/mL. Tests on E. coli bacteria showed the highest results in a single white tea extract with a diameter of 9.750 mm, and tests on S. aureus showed the highest results in the three tea extract formula with a diameter of 9.65 mm. The inhibitory area evaluation of the system changed into finished using the simplex-centroid design method. It showed a non-huge linear model in the antibacterial test in opposition to E. coli and S. aureus.